Breaking the Glass Ceiling: Mentoring as Support for African Women’s Academic Career Trajectories - Renitha Rampersad (African Journal of Inter-Multidisciplinary Studies)
Women in academia face many challenges. Although there have been possibilities for the advancement of women in higher education, gender discrepancies in leadership continue, with women facing structural challenges such as bias, and unequal possibilities for promotion. Balancing a career as a female academic, including parenting and family obligations adds another layer of complication, often resulting in breakdown. Women contribute distinct strengths to academia, expanding intellectual conversation and establishing varied learning environments. Mentorship, sponsorship, and inclusive policies assist in reducing barriers and encourage women to thrive as leaders, resulting in positive change in the academic setting. The article outlines the nuances of women in academia and the challenges and opportunities they face when pursuing leadership positions.  It further explores the experiences and views of women in the faculty of Business at a University of Technology (UOT). A mixed methods approach was adopted to enable the researcher to give a female perspective to the academic position, experiences, and challenges within academia. The researcher used her judgment to select the sample based on the purpose of the research and a convenience sample to select best-case scenarios. Finally, the article suggests a participative model of collaboration, nurturance, compassion, and self-care to equip women with the tools they need to create career advancement opportunities and increase personal and professional change.